An Atlas of Radioscopic Catheter Placement for the Electrophysiologist - Casella, Michela; Dello Russo, Antonio; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2008)
The heart is a four-dimensional structure, comprising three spatial dimensions of shape and one temporal dimension of motion. Many technological advances in the field of imaging, such as intracardiac echocardiography, computed tomography, magnetic resonance imaging and 3-D electroanatomical image integration mapping systems, have enhanced our ability to visualize, map, and navigate in the heart. Nevertheless, fluoroscopy remains the cornerstone of all interventional electrophysiology procedures and, with the limitations of current technologies, will continue to be extensively used for many years to come. A skilled fluoroscopist with the use of multiple projections can deduce the anatomy and catheter location with remarkable spatial detail. However, since fluoroscopy provides a real-time unmodified view to the operator, there is no easy way to organize the multiple measurements taken from a moving catheter into a more clinically useful model of cardiac electrical activity. As a result, significant clinical experience with fluoroscopy is necessary to accurately position catheters at an exact intracardiac site. Atlas of Radioscopic Catheter Placement for the Electrophysiologist is unique because it is the first book that provides a teaching tool for fellows in training, allied health professionals and accomplished electrophysiologists on relevant X-ray views commonly encountered in different electrophysiology procedures, and how these views correlate with cardiac anatomy. It was specifically designed to address this challenging aspects of all electrophysiology procedures systematically and is written in a perspicuous manner to demystify the subject, thus making it easier to better understand cardiac anatomy and successfully perform electrophysiology procedures.
Radiology -- X-Ray Anatomy of the Heart -- Computed Tomography of Anatomy of the Heart -- Electrophysiology -- The Electrophysiologic Study -- Ablation of Supraventricular Tachycardias from the Right Atrium -- Approach to the Left Heart Chambers -- Accessory Pathways Ablation -- Atrial Fibrillation Ablation -- Ventricular Tachycardia Ablation -- Pacing -- Pacemaker and Implantable Cardioverter-Defibrillator Implantation -- Biventricular Pacemaker and Implantable Cardioverter Defibrillator -- Pacemaker and Implantable Cardioverter Defibrillator Lead Extraction -- Endomyocardial Biopsy -- Endomyocardial Biopsy.
Keywords: Cardiology; Cardiac surgery; Radiology; Internal medicine; Emergency medicine; Cardiology; Cardiac Surgery; Imaging / Radiology; Internal Medicine; Emergency Medicine